The Role of IT-Based Quality Assurance Systems in Higher Education: A Global Perspective - Ansori, Ahmad; Saputra, Nanda; Sholikha, Dian Nikmatus; Juliani, Dwi (International Journal of Education, Information Technology, and Others, 2024)
This study aims to analyze the concept of quality assurance systems in higher education, explore the implementation of technology-based quality assurance systems in universities across various countries, and understand the role of information technology in strengthening these quality assurance systems. This review also aims to identify the various types of quality assurance present in higher education institutions, as well as the technologies or applications used to support these systems. The method employed is qualitative with a literature study approach, involving the collection and analysis of data from various written sources, including books and scholarly articles. The results indicate that quality assurance systems in higher education represent a systematic and continuous approach that includes the establishment, implementation, evaluation, control, and improvement of quality standards. Information technology plays a crucial role in enhancing efficiency, transparency, and accountability in the quality assurance process, as well as supporting faster and more effective accreditation evaluations. Although the implementation of technology-based systems offers numerous advantages, such as improved graduate quality and easier access to information, challenges such as infrastructure limitations, the need for skilled human resources, and data protection must still be addressed. Therefore, higher education institutions need to adapt to technological advancements and formulate appropriate strategies to optimize the implementation of technology-based quality assurance systems, in order to enhance the overall quality of higher education and meet the expectations of all stakeholders.